Abiotic modulators of Podocnemis unifilis (Testudines: Podocnemididae) abundances in the Peruvian Amazon - Norris, Darren [UNESP]; Pitman, Nigel C.A. [UNESP]; Martínez Gonzalez, Jerry; Torres, Eriberto; Pinto, Fernando; Collado, Hernán; Concha, Wilberth; Thupa, Raúl; Quispe, Edwin; Pérez, Jorge; Flores del Castillo, Juan Carlos (Sociedade Brasileira de Zoologia, 2011)
Previous studies have demonstrated that river-based surveys can provide an inexpensive source of information for neotropical zoologists, yet little information is available to inform the application of this technique for the long term monitoring of neotropical turtle species. We aimed to fill this gap by presenting an assessment of data collected during 333 river surveys over 50 months along rivers in a newly protected area in the Peruvian Amazon. A total of 14,138 basking Podocnemis unifilis Troschel, 1848 were recorded during 13,510 km of river-based surveys. We used generalized additive models (GAMs) to explore the influence of a series of abiotic and seasonal variables on the recorded abundances at two temporal scales: monthly and per trip. Our analysis revealed that there was a significant increase in turtle abundances during the study period and we also found a significant seasonal periodicity in monthly abundances. Abiotic factors strongly influenced trip level abundances, with more individuals per kilometer recorded during sunny days in the dry season, with temperatures between 25 and 30°C. The results demonstrate that turtle populations are increasing following the establishment of the protected area and that river-based surveys are likely to be more effective when carried out within a limited set of key abiotic conditions.
Keywords: Basking survey; conservation; population monitoring; river turtles; sighting rates